The Impact of Lifestyle Factors on Arterial Blood Pressure and Its Control in Hypertensive Patients (Razi Medical Journal, 2025)
Hypertension, a major global health challenge, is the leading preventable risk factor for cardiovascular diseases. Lifestyle choices—particularly unhealthy diets, physical inactivity, and obesity—play a central role in both its progression and control. These modifiable behaviors drive physiological changes that elevate blood pressure, underscoring the importance of targeted interventions to mitigate cardiovascular risks worldwide. This cross-sectional study examines the association between lifestyle factors—including physical inactivity, obesity, fast food consumption, and smoking—and blood pressure levels among 302 adults in Zawia City, Libya. The analysis revealed significant associations between elevated blood pressure and older age (χ² = 31.773, p< 0.001), lower educational attainment (χ² = 13.756, p = 0.008), and obesity (χ² = 12.124, p = 0.007). Physical activity and vegetable consumption exhibited borderline statistical significance, suggesting potential protective effects. However, no significant associations were observed with gender, marital status, fruit intake, fast food consumption, or smoking, indicating that demographic and body mass index (BMI)-related factors may be more influential in this population. These findings underscore the importance of obesity management, age-specific interventions, and targeted health education for individuals with lower socioeconomic status. The study aligns with existing global evidence on modifiable hypertension risk factors and recommends promoting physical activity, weight control, and diets rich in vegetables. Further longitudinal research is needed to elucidate the observed non-significant trends and strengthen causal inferences.
Keywords: Hypertension, Cardiovascular Diseases, Lifestyle Factors, Cross-Sectional Study